FISHBONE PEMANFAATAN KEUNGGULAN DAPUR HALAL SEBAGAI ALAT OPTIMALISASI PEMASARAN DI RUMAH SAKIT ISLAM UNISMA MALANG - Rizki Rachmat, Kiki (Jurnal Administrasi Publik, 2024)
Fish Bone Utilizing The Advantages Of Halal Kitchen As A Marketing Optimalisation Tool At UNISMA Malang Islamic Hospital. As shown by the presence of sharia hospitals in Indonesia, the awareness of halal lifestyle has increased among the predominantly Muslim Indonesian society. Marketing is one way for healthcare professionals to introduce their services to the general public or specific target markets. The preliminary study was conducted through a primary data search process, which included direct interviews with resource persons in several work units and observation of the work unit environment. Problems were identified with fish frames and five reasons, and solutions were sought by conducting observations, literature studies, brainstorming, and benchmarking in other hospitals and CARL for problem prioritisation. There is no specialised training on halal kitchen marketing. To ensure that Muslim customers around the world are protected, certification and halal marking of products are of great concern in the international trading system. Unisma, which has been officially Halal certified, suggests to make a simple halal kitchen tent and evaluate the marketing unit periodically.